A small garage on the sidelines of a corporation: Should innovative projects be isolated? - Kamiński, Robert; Rosłoń, Robert (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article aims to attempt to answer the question of whether innovative projects should be isolated in an organisation. A critical analysis of the literature on the subject reveals a divergence of views on the proper placement of social or technological innovation projects. The research hypothesis formulated holds that the more conducive the innovative project team is to interact with the rest of the organisation and the norms and values within the team are oriented toward learning, the stronger the learning of the project team. The culture metaphor of an organisation was used to verify the research hypothesis. It has been assumed that project team learning means that project team members transform the norms and values previously adhered to in the organisational culture. On the basis of the survey results, it was impossible to accept the research hypothesis. Despite the increase in the intensity of the factors that foster interactions between teams implementing innovative projects and the rest of the organisation, team learning did not increase as originally expected.
Keywords: project management; organisational culture; learning